From Teacher Talk to Embodied Actions: Investigating an EFL Primary School Teacher’s Classroom Interactional Competence - Ahmad Sugianto; Sarah Fawziah Khoirunnisa (Yayasan Visi Intan Permata, 2024)
Teacher talk and embodied actions constitute an essential aspect to facilitate students’ learning and learning opportunities in EFL classroom interactions. Nevertheless, evidence has shown that the ways an EFL teacher employs teacher talk and embodied actions are still under-explored, particularly in the Indonesian EFL primary school context. Therefore, the present study is aimed at scrutinising an EFL primary school teacher's use of embodied actions along with teacher talk that leads to classroom interactional competence. Using a conversational analysis approach, the present study inspected six naturally occurring lessons conducted by a female English teacher teaching in the fifth grade. Twenty-six students were involved as the subjects. Moreover, the data of the current study were garnered using observations and included the teacher’s instructional artifacts. Findings reveal some embodied actions were used by the teacher during the classroom interactions. In this case, the teacher’s gazes were found to be directed at a particular student, a group of students, and objects in the classroom. Also, such gazes were found to be accompanied by deictic gestures, metaphoric gestures or beats that were used by the teacher to elicit responses from the students. Moreover, iconic gestures were also found in the data as the teacher was trying to introduce a new vocabulary. The present study reaches a conclusion that most of the interactional features found in conformity with the pedagogical goals for each micro-context or mode were used to support and mediate the students’ learning